Factors that contribute to the phosphorus fixation capacity of soils from the municipality of Piracicaba - Thomazi, M.D.; Mello, F.de A.F.de; Arzolla, S. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1990)
Phosphate fixation capacity of soils from the municipality of Piracicaba, State of Sao Paulo, Brazil, was studied under laboratory conditions. The main conclusions are as follows. Clay and free iron oxides are the main factors contributing to P fixation by the soils from the municipality of Piracicaba. Gibbsita must be important for the Iracema Serie. In all cases sand contributed to reduce P fixation. Fixation capacity of the soils studied decreased as follows: Iracema >; Luiz de Queiroz >; Monte Olimpo >; Lageadinho >; Pau D'Alho >; Quebra Dente = Gibóia >; Ribeirão Claro. After incubation with 250ppm of P, the soils still continued to retain this element but none of the studied factors correlated with the fixed amounts with the exception of sand which correlated negatively.